The Persuasiveness of Pleasure: Play, Reciprocity, and Persuasion in Online Discussions - Sue Hum (Journal of the Assembly for Expanded Perspectives on Learning, 2008)
This essay explores the role of pleasure in facilitating diverse modes of rhetorical participation in online discussion.